Daya Bunuh Kelambu Berinsektisida Long Lasting Insecticidal Nets (LLINS) terhadap Nyamuk Anopheles maculatus - Rizki Nurmaliani; Reni Oktarina; Maya Arisanti; Desy Asyati (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Malaria is one of the infectious diseases that become a public health problem that can be a major cause of death in developing countries, especially in infants, toddlers, and pregnant women. Nowadays, malaria caseis still commonly found in Ogan Komering Ulu (OKU) South Sumatera Province. One of the efforts in malaria prevention and control that Health Office of OKU District has been carrying out was the distribution of Long Lasting Insecticidal Nets (LLINS). This study aimed to obtain the percentage of mosquito mortality in order to assesslethal potency of LLINs that have been distributed by the Health Office of OKU District and was still used by the community. This study was an observational research with cross sectional design. The percentage of mosquito mortality rate was obtained through bioassay test on LLINs that randomly selected from the community in Bumi Kawa village in Lengkiti of OKU District. The mosquitoes that used for the test were Anopheles maculatus that were bred and reared in the laboratory. Long Lasting Insecticidal Nets (LLINs) were grouped based on the duration of use(2-3 years and above 3 years) and the frequency of washing(unwashed, once, twice, and thrice). The results showed that all nets had mosquitos’ knockdown less than 95% and the mortality less than 80% of mosquitoes. These numbers showed that all the tested nets are no longer effective in killing mosquitoes.